Interaksi antara Status Indeks Massa Tubuh sebelum Hamil dan Kenaikan Berat Badan selama Hamil terhadap Antropometri Bayi Lahir di Sumatera Barat, Indonesia: The Interaction between Pre-Pregnancy Body Mass Index Status and Gestational Weight Gain on Newborn Anthropometry Outcomes in West Sumatera, Indonesia - Anugerahwati, Ammara Asya; Aji, Arif Sabta; Afifah, Effatul; Lestari, Prasetya; Lipoeto, Nur Indrawaty (Amerta Nutrition, 2024)
Background: Mother's nutritional status before and during pregnancy plays an important role in fetal growth and development. The prevalence of Low Birth Weight (LBW) incidence in West Sumatra has increased from 3.11% (2019) to 3.4% (2021). Objectives: To analyze the interaction between pre-pregnancy BMI status and gestational weight gain on newborn anthropometry in West Sumatra. Methods: This is a secondary data analysis study from the Vitamin D Pregnant Mother (VDPM) 2018 study with a prospective cohort design and the follow-up analysis was in February-April 2024. This study involved 175 pregnant women and newborns who met the predetermined criteria. Variables examined included pre-pregnancy BMI status, gestational weight gain, and newborn anthropometry. Data analysis used Kruskal Wallis, Spearman correlation test, and multivariate General Linear Model (GLM). Results: Research findings showed a correlation between pre-pregnancy BMI and gestational weight gain (p-value 0.049, r=-1.4). Pre-pregnancy BMI correlated with birth weight (p-value=0.003, r=0.2) and body length (p-value=0.045, r=0.1), but not with head circumference (p-value=0.054). Gestational weight gain had no significant relationship with newborn anthropometry (p-value 0.512 for birth weight, p-value 0.368 for body length, and 0.368 for head circumference). No interaction was found between pre-pregnancy BMI and gestational weight gain status on newborn anthropometric measurements with a p-value of 0.739 for birth weight, 0.377 for body length, and 0.175 for head circumference. Conclusions: The results show no interaction between pre-pregnancy BMI status and gestational weight gain on newborn anthropometry. Women are encouraged to pay attention to nutrition before and during pregnancy to optimize maternal and infant health.